The New Christian Right’s relations with Israel and with the American Jews: the mid-1970s onward - Mokhtar BEN BARKA (E-REA)
The aim of this article is to show that the relationship between the New Christian Right and Jews is complicated and even controversial. Adherents of the New Christian Right are known to be staunch supporters of Israel. Their love for the State of Israel stems from biblical teachings asserting that God blesses those who bless the Jews and curses those who curse the Jews (Genesis, 12:3). Yet the evangelical view of Israel and of Jews is a source of considerable debate within the Jewish community. Many Jews have reservations about teaming up with evangelicals: they suspect their motives and resent their interpretation of Bible prophecies suggesting that Jews will have to accept Christ after his Second Coming. In the meantime, evangelicals target them for evangelism.